1986
DOI: 10.1080/09553008614551001
|View full text |Cite
|
Sign up to set email alerts
|

‘Fading Times’ Required for Apparently Complete Repair in Irradiated Tissues Assuming the Linear Quadratic Model of Dose Response

Abstract: The time required between well-separated pairs of doses of X-rays (e.g. 2F/day) for repairable damage to be apparently completed increases with dose per fraction and with the alpha/beta ratio, even when the underlying half-life is invariant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Animal studies indicate that the repair half‐time in many tissues is around 1–1.5 hr 18. Clinical results provide confirmatory evidence indicating that intervals below 4 hr may be associated with an unacceptable incidence of delayed toxicity to normal tissue 19, 20. Moreover, Short et al 21 reported that 4 hr are needed between 2 irradiations to allow the HRS to be conserved.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Animal studies indicate that the repair half‐time in many tissues is around 1–1.5 hr 18. Clinical results provide confirmatory evidence indicating that intervals below 4 hr may be associated with an unacceptable incidence of delayed toxicity to normal tissue 19, 20. Moreover, Short et al 21 reported that 4 hr are needed between 2 irradiations to allow the HRS to be conserved.…”
Section: Resultsmentioning
confidence: 90%
“…18 Clinical results provide confirmatory evidence indicating that intervals below 4 hr may be associated with an unacceptable incidence of delayed toxicity to normal tissue. 19,20 Moreover, Short et al 21 reported that 4 hr are needed between 2 irradiations to allow the HRS to be conserved. Therefore, we tested an ultrafractionated regimen: 3 fractions of 0.8 Gy spaced by 4 hr compared to the biologically equivalent single dose of 2 Gy on G5, CL35, G152 and MRC5 (we determined that 4.8 Gy for hyperfractionation is roughly biologically equivalent to 4 Gy for conventional fractionation by graphically determining ␣/␤ assuming that the curve did not have a dip at 0.8 Gy, i.e., was following the LQ model).…”
Section: Cumulative Effect Of Low Radiation Doses On Cell Survivalmentioning
confidence: 99%
“…6 h intervals, between 3F/d (36F/12 d) for bronchial carcinoma (Saunders and Dische 1986) . It is in principle necessary to allow four or five half-lives between doses per fraction (Fowler 1986), and in practice 6 h rather than 4 appears to be necessary (Marcial et al 1987) . For this application the slowest component present is important .…”
Section: Discussionmentioning
confidence: 99%